2017
DOI: 10.1111/trf.14015
|View full text |Cite
|
Sign up to set email alerts
|

Spherocytic shift of red blood cells during storage provides a quantitative whole cell–based marker of the storage lesion

Abstract: The reduction in surface area of small RBCs is expected to induce their retention by the spleen. We propose that small RBCs generated by MP-induced membrane loss are preferentially cleared from the circulation shortly after transfusion of long-stored blood. Their operator-independent quantification using imaging flow cytometry may provide a marker of storage lesion potentially predictive of transfusion yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 47 publications
4
91
0
3
Order By: Relevance
“…2) were constructed with twodimensional thresholds (i.e., ROI-based gating), which helped us achieve more accurate delineations of less discernable subpopulations. RBC morphology characterization with the Imag-eStreamX ® /IDEAS ® system has been previously investigated by Roussel et al; they observed a strong correlation between the increase in small-diameter RBCs (inferred as SECs) captured on the IFC platform and RBC storage lesion populations observed through LM (42). In comparison, the novelty in our IFC template lies in the ability to distinguish, directly, RBC subclasses based on the standard LM morphology classification guidelines (19,20)).…”
Section: Comparative Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…2) were constructed with twodimensional thresholds (i.e., ROI-based gating), which helped us achieve more accurate delineations of less discernable subpopulations. RBC morphology characterization with the Imag-eStreamX ® /IDEAS ® system has been previously investigated by Roussel et al; they observed a strong correlation between the increase in small-diameter RBCs (inferred as SECs) captured on the IFC platform and RBC storage lesion populations observed through LM (42). In comparison, the novelty in our IFC template lies in the ability to distinguish, directly, RBC subclasses based on the standard LM morphology classification guidelines (19,20)).…”
Section: Comparative Analysismentioning
confidence: 76%
“…Flow morphometry techniques, such as the fluidic system by Sierra et al, acquire high-throughput LM images of RBCs in flow suspension (41). RBC morphology characterization with the Imag-eStreamX ® /IDEAS ® system has been previously investigated by Roussel et al; they observed a strong correlation between the increase in small-diameter RBCs (inferred as SECs) captured on the IFC platform and RBC storage lesion populations observed through LM (42). In comparison, our binary trees (Fig.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Measurements reported elsewhere on the extent of the DEHP interaction with the RBC membrane in transfusion bags [3] suggest that the DEHP-to-lipid ratio is sufficiently high to affect the lipid-based membrane physical properties [39]; the ratio in the stomatocytes seen here may be in a similar range, as suggested by the calculation of stomatocyte counts formed after exposure to stirred DEHP. The RBC suspensions in transfusion bags have been shown to have a relatively high proportion of stomatocytes over the majority of the storage period [45]. This may be due to a combination of factors including the pH of the storage medium.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and size (i.e., projected surface area) of RBC are related to their ability to persist in circulation through their impact on the surface-to-volume ratio (Mohandas et al, 1980;Jaureguiberry et al, 2014;Pivkin et al, 2016). As an illustration, IFM has recently revealed that storage of RBC in blood bank conditions induces a spherocytic shift of some RBC due to a surface area loss (Roussel et al, 2017(Roussel et al, , 2018. These "storage-induced micro-spherocytes" are removed from the circulation (Roussel, 2019).…”
Section: Imaging Flow Cytometrymentioning
confidence: 99%